2016
DOI: 10.1186/s13195-016-0226-6
|View full text |Cite
|
Sign up to set email alerts
|

LW-AFC, a new formula derived from Liuwei Dihuang decoction, ameliorates behavioral and pathological deterioration via modulating the neuroendocrine-immune system in PrP-hAβPPswe/PS1ΔE9 transgenic mice

Abstract: BackgroundAccumulating evidence implicates the neuroendocrine immunomodulation (NIM) network in the physiopathological mechanism of Alzheimer’s disease (AD). Notably, we previously revealed that the NIM network is dysregulated in the PrP-hAβPPswe/PS1ΔE9 (APP/PS1) transgenic mouse model of AD.MethodsAfter treatment with a novel Liuwei Dihuang formula (LW-AFC), mice were cognitively evaluated in behavioral experiments. Neuron loss, amyloid-β (Aβ) deposition, and Aβ level were analyzed using Nissl staining, immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 106 publications
1
23
0
Order By: Relevance
“…A number of drugs targeting Aβ clearance (such as Aβ antibodies) or production (such as Aβ secretase inhibitors) have proceeded to clinical trials, but most of them failed to improve the cognitive functions in patients, which are mainly attributed to the signal targets, side effects, or the neuroinflammatory responses of these drugs ( 9 , 10 ). By contrast, many traditional medicines and natural products have shown great progress toward AD prevention and treatment ( 11 , 12 ). These studies also shed new light on the discovery and development of useful agents from established traditional medicines and safe natural products to halt the progression of neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
“…A number of drugs targeting Aβ clearance (such as Aβ antibodies) or production (such as Aβ secretase inhibitors) have proceeded to clinical trials, but most of them failed to improve the cognitive functions in patients, which are mainly attributed to the signal targets, side effects, or the neuroinflammatory responses of these drugs ( 9 , 10 ). By contrast, many traditional medicines and natural products have shown great progress toward AD prevention and treatment ( 11 , 12 ). These studies also shed new light on the discovery and development of useful agents from established traditional medicines and safe natural products to halt the progression of neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration of innate immune-mediated mechanisms and the use of immunomodulation as a disease-modification strategy have been promising in the preclinical research of AD [11]. Animal studies have shown that targeting the innate immune molecules or their respective signaling pathways may substantially ameliorate AD-related pathology [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Exploration of innate immune-mediated mechanisms and the use of immunomodulation as a disease-modi cation strategy have been promising in the preclinical research of AD [11]. Animal studies have shown that targeting the innate immune molecules or their respective signaling pathways may substantially ameliorate AD-related pathology [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%